Effectiveness of Collection of Land and Building Tax in the Rural and Urban Sector (PBB-P2) Receivables in Increasing the Realization of Revenue in the Revenue Agency of Bekasi City Area in 2019-2021 - Citra Novlyani; Dinda Annisa Darmawan (Yayasan Ilomata, 2022)
Local taxes are taxes collected and managed by local governments to fund all government functions and local development. The Local Revenue Board is a local apparatus that functions to manage all types of revenue and local wealth income, one of which is Land and Building Tax in the Rural and Urban Sector (PBB-P2). The high amount of PBB P2 receivables in Bekasi City is due to problems in the implementation of tax collection. This research was conducted to determine the effectiveness of the PBB-P2 Receivable Collection in Bekasi City and the obstacles and efforts done in the collection of PBB-P2. The researcher used research methods descriptive qualitative. Data collection from this research is by interview, observation, and documentation. The result of this research shows that the effectiveness of Land and Building Tax in the Rural and Urban Sector collection of receivables in increasing the realization of Revenue is less effective when viewed from the non-achievement of the revenue target in 2021 with a percentage of 77.46% and the high number of PBB-P2 receivables which continues to increase every year. Less effective collection of PBB-P2 receivables in the City Bekasi is caused by several obstacles that occur such as lack of awareness of taxpayers, uneven socialization, lack of quality and quantity of human resources, and limited facilities and infrastructure. The efforts made by the Local Revenue Board of Bekasi City are to socialize along with banks to make it easier for taxpayers to make payments and cooperate with the Executive Unit for Integrated Service of sub-districts, villages, and neighborhood/hamlets.